2000
DOI: 10.2337/diacare.23.7.984
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the performance of commercially available 10-g monofilaments.

Abstract: OBJECTIVE: This independent study was designed to determine the accuracy of 10-g monofilaments manufactured and supplied by popular commercial companies. RESEARCH DESIGN AND METHODS: A total of 160 new 10-g monofilaments (30 Semmes-Weinstein monofilaments [North Coast Medical], 30 Timesco/Sensory Testing Systems monofilaments, 50 Owen Mumford Neuropens, and 50 Bailey Instruments monofilaments) were tested using a calibrated load cell. Each monofilament was subjected to 10 mechanical bucklings of 10 mm while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 25 publications
0
75
0
9
Order By: Relevance
“…This considerable difference has been studied extensively before, pointing out some general problems inherent in the Semmes-Weinstein monofilament set: (1) the discontinuous scale of the Semmes-Weinstein monofilament test does not allow precise measurement; (2) the problem of measuring a force threshold rather than a pressure threshold; (3) the inability to know the true surface area in contact with the skin at the moment the filament buckles; (4) the variance in manufacturing allowing a 10 percent error in the initial applied force of the filaments; and (5) the fatigue of the nylon with more than 100 uses. 23,[38][39][40][41][42] These circumstances led to the conclusion that normative data are impossible to generate for the Semmes-Weinstein monofilament, thus harshly limiting its intrainstrument and interinstrument comparability. Indeed, the PressureSpecified Sensory Device clearly compensates for most of the mentioned points of criticism: it is measured on a continuous scale (with "open ends"), which even captures extreme values and outliers reliably; whereas the Semmes-Weinstein monofilament test is limited to five grades, potentially neglecting higher or lower values, thus pretending a smaller variance.…”
Section: Discussionmentioning
confidence: 99%
“…This considerable difference has been studied extensively before, pointing out some general problems inherent in the Semmes-Weinstein monofilament set: (1) the discontinuous scale of the Semmes-Weinstein monofilament test does not allow precise measurement; (2) the problem of measuring a force threshold rather than a pressure threshold; (3) the inability to know the true surface area in contact with the skin at the moment the filament buckles; (4) the variance in manufacturing allowing a 10 percent error in the initial applied force of the filaments; and (5) the fatigue of the nylon with more than 100 uses. 23,[38][39][40][41][42] These circumstances led to the conclusion that normative data are impossible to generate for the Semmes-Weinstein monofilament, thus harshly limiting its intrainstrument and interinstrument comparability. Indeed, the PressureSpecified Sensory Device clearly compensates for most of the mentioned points of criticism: it is measured on a continuous scale (with "open ends"), which even captures extreme values and outliers reliably; whereas the Semmes-Weinstein monofilament test is limited to five grades, potentially neglecting higher or lower values, thus pretending a smaller variance.…”
Section: Discussionmentioning
confidence: 99%
“…A final caution on the use of the filaments: Booth and Young (173) identified that filaments manufactured by certain companies do not actually buckle at 10 g of force. Indeed, several tested filaments buckled at Ͻ8 g. Thus, care must be taken when selecting suppliers of filaments.…”
Section: Clinical Assessment Of Dpnmentioning
confidence: 99%
“…The 10-g monofilament, used to test pressure perception, is frequently employed to assess diabetic patients' foot ulcer risk status [40]. Although simple to perform, care must be taken to ensure that the filaments used are accurate in delivering a 10-g force when used [41]. Moreover, it has also been suggested that the widespread use of filaments needs to be reappraised as this may not be the most sensitive test [42].…”
Section: Causal Pathways To Foot Ulcerationmentioning
confidence: 99%